Literasi Manajemen Teknologi Melalui Pengembangan Marketplace pada Usaha Sparepart Personal Computer Second Jambi - Prayetno Agustinus Sitanggang; Friska Artaria Sitanggang; Jonner Simarmata; Christi Maharaja (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This Community Service activity aims to enhance technology management literacy among small business owners of second-hand computer PC spare parts through training and mentoring in the use of the Shopee marketplace. Shopee was chosen as the digital marketing platform because it is one of the largest and most widely accessed marketplaces in Indonesia. Many micro-entrepreneurs still lack comprehensive knowledge of digital strategies, including online store management, product display, and promotional features on Shopee. Therefore, this program is designed to equip participants with practical knowledge and skills to fully utilize Shopee. The implementation method includes needs identification, digital literacy training, hands-on workshops, and intensive mentoring. Evaluation is conducted to measure the participants’ competence in independently managing a marketplace-based business in a sustainable manner.